Asset Restitution Reform to Ensure Legal Protection and Fairness for Investors - Deni Setiyawan; Muhammad Nurcholis Alhadi; Chami Yassine (Journal of Law and Legal Reform)
Emerging concerns in the legal domain are a direct result of the digital age's advancements in the economic sphere. Binary options' rise to prominence is a topic worthy of discussion, particularly with regard to the breadth of asset returns in such instances. Binary option victims are questioning the fairness of the state's claim to assets in light of the recent court ruling in the Indra Kenz and Doni Salmanan case. This research aims to help victims of binary options get their money back through restitution by analyzing the problem and offering remedies. The victims of binary option crimes will have their rights protected; that much is certain. Solutions to the problem of investor asset return can be found by using normative methodologies in the examination of statutes, case studies, and concepts. This study finds that victims of illegal activities can regain their possessions through restitution, which also provides a sense of justice and guarantees legal protection for their rights. People can suffer materially, emotionally, and psychologically as a result of committing a criminal offense. Based on the priorities of legal protection and justice, this research is anticipated to provide a solution for law enforcement in the return of assets for binary option criminal offenses.